FORKING DALAM GITHUB, DILEMA DALAM IMPLEMENTASI HAK KEKAYAAN INTELEKTUAL PERANGKAT LUNAK - Wicaksono, Soetam Rizky (IBLAM LAW REVIEW, 2021)
Protection of software has been protected in the 2014 copyright law, particularly in article 45. However, the recognized copyright is an existing computer program as well as a copy of the program itself. This protection is not fully guaranteed, because in software, the elements that make up the product can consist of various source code (program listings). Because it could be that a registered computer program is the result of forking from Github or the result of a clone which is then modified. For non-programmers, this activity may be sentenced as a frontal copyright infringement, but in fact, it has become a new habit for programmers. But on the other hand, there are still many forked software which are later claimed to be new products, even registered as new copyrights. The Copyright Law itself does not specifically regulate the provisions for program listings, as well as the ITE Law. Therefore, this article describes different points of view on the protection of software intellectual property rights, especially for the forking process. So that the ambiguity of the forking results can be minimized and the programmers can be aware of which ones are eligible to become new copyrights. There should also be a revision of the Copyright Law and there must be more jangintensive socialization to the programmer community so that they are aware and understand about the risks of forking and what must be protected from their work.